Use of glycerol coating to control aflatoxin production by Aspergillus parasiticus in peanut grains - Juliana F. Moreira da Silva; Camilla Martins Malta; Joenes Mucci Peluzzio; André Faraco; Guilherme Prado; Jovita Eugênia Gazzinelli Cruz Madeira; Marize Oliveira Silva; Jaques Robert Nicoli; Raphael Sanzio Pimenta (São Paulo State University (UNESP), 2015)
Peanut grains are very susceptible to aflatoxin contamination. Aflatoxins are toxic metabolites produced by Aspergillus flavus, A. nomius and A. parasiticus. The aflatoxin B 1 is most frequently found in peanuts, posing a high toxicological risk due to its carcinogenic, teratogenic and mutagenic properties. Alternative methods to fungicides can be used to protect grains. GRAS (Generally Regarded As Safe) substances can be an interesting option to avoid contamination, specially glycerol. In the present work, the ability of glycerol films to prevent aflatoxin production by A. parasiticus in peanuts was evaluated. Glycerol was established in two different ways: by immersion and aspersion. Aspersion was more efficient in reducing aflatoxin production (86.3%) than was the immersion process (66.9%) (P < 0.05). At the same time, a progressive reduction in A. parasiticus colony diameters was observed (from 38.6 ± 0.9 to 34.4 ± 1.7 mm) when the fungus was grown on GYEP medium supplemented with glycerol (0 to 5%). However, varying concentrations did not influence the production of spores, colonies, conidiophores or spore condition. Peanuts coated with 5% glycerol (by immersion or aspersion) had improved characteristics, with a cleaner and more shiny appearance, which can make the resulting product more acceptable to the population. In conclusion, the reduction of aflatoxin production in peanut grains with glycerol, particularly by aspersion, was satisfactory, and this GRAS substance shows promising potential to be used to prevent mycotoxin contamination in grains.